Breakfast consumption was associated with suicidal ideation, plan, and attempt: a population-based cross-sectional study - Zhang, Yunshu; Li, Keqing; Zhang, Lili; Sun, Long (Frontiers in Public Health, 2024)
BackgroundAlthough several studies have explored the association between breakfast consumption and suicidal behaviors among children and adolescents, such associations have been less frequently reported among adults and seniors.MethodThis population-based cross-sectional study was conducted in Hebei Province, China. A total of 21, 376 community residents aged 18 years and older were interviewed. This study evaluated the breakfast frequency per week (BFF), full breakfast frequency (FBF), suicidal ideation, suicide plans, and suicide attempts of the participants. Sociodemographic variables, living alone, and sleep quality were also measured.ResultsThe prevalence of suicidal ideation, plans, and attempts were 1.4, 0.3, and 0.2%, respectively. Compared to ≥6 days/week BFF, 2–3 days/week BFF was positively associated with suicidal ideation (OR = 1.93, p < 0.01), suicide plan (OR = 2.73, p < 0.05), and suicide attempts (OR = 3.46, p < 0.05). In addition, participants with 2–3 days/week FBF was also at higher risk of suicidal ideation (OR = 2.06, p < 0.001), comparing with never FBF.ConclusionThe reported prevalence of suicidal ideation, plans, and attempts were lower compared to other countries. Lower breakfast frequency was positively associated with suicidal behaviors, and participants with 2–3 days/week of full breakfast consumption were also at a higher risk of suicidal ideation.